2012
DOI: 10.1007/s10853-012-6619-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mg dopant on the electrochemical performance of LiNi0.5Co0.5O2 cathode materials for lithium rechargeable batteries

Abstract: Positive electrode materials, LiMg x Ni 0.5-x Co 0.5 O 2 (x = 0 \ x \ 0.5), have been successfully synthesized by microwave-assisted solution technique. The precursor has been analyzed by TG/DTA and the powder was calcined at 850°C. The XRD patterns reveal that the synthesized materials exhibit hexagonal layered structure corresponding to R3m space group. Coin cells of 2016 type have been fabricated using the synthesized layered material as cathode active material and lithium foil used as counter and reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…X‐ray photoelectron spectroscopy (XPS) of bentonite@Cl in Mg, Na, Ca, Al, Si, Cl, C, and O were studied. The XPS spectrum of Mg 1s showed a peak at 1302 eV confirming the presence of Mg(II) in the structure of bentonite (Figure a) . The binding energy observed for Na 1s is 1071.9 eV, which is characteristic of Na(I) oxidation state (Figure b) .…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…X‐ray photoelectron spectroscopy (XPS) of bentonite@Cl in Mg, Na, Ca, Al, Si, Cl, C, and O were studied. The XPS spectrum of Mg 1s showed a peak at 1302 eV confirming the presence of Mg(II) in the structure of bentonite (Figure a) . The binding energy observed for Na 1s is 1071.9 eV, which is characteristic of Na(I) oxidation state (Figure b) .…”
Section: Resultsmentioning
confidence: 74%
“…By increasing reaction time to 45 and 60 min, 33 and 71 % yields were obtained, respectively (Table 1, entries [11][12]. Then, the catalyst amount was increased to 0.06 and 0.1 mol % and the progress of the reaction at different times were studied (Table 1, entries [13][14][15]. Results indicated that using 0.1 mol % catalyst in 30 min afforded quantitative yield for the reaction (Table 1, entry 15).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high capacity delivering anode material are needed to stabilise structurally during charge-discharge due to the large volume expansion, on the other hand high capacity cathode materials require crystal structural stability and electronic conductivity which have been studied by many researchers. [27][28][29] Since the wide range of studies in RGO-SnO 2 and other RGO-metal/metal oxide [22][23][24][25][26] materials as anodes for lithium ion batteries, graphene based materials finds a unique place due to their superior properties. For the first time, we report the organic solvent exfoliation of graphite using NMP and the synthesis of an SnO 2 nanocomposite, made from the brownish graphene dispersed NMP transparent medium, via the co-precipitation method and annealing at 350 1C at ambient conditions.…”
Section: Introductionmentioning
confidence: 99%